Synthesis and physical properties of lipid-based poly(ester-urethane)s, I: Effect of varying polyester segment length - Hojabri, Leila; Jose, Jesmy; Leão, Alcides Lopes [UNESP]; Bouzidi, Laziz; Narine, Suresh S. (Elsevier B.V., 2012)
Four aliphatic thermoplastic poly(ester-urethane)s (PEUs) with similar molecular weights but varying polyesters molecular weight (534-1488 g/mol) were prepared from polyester diols, obtained by melt condensation of Azelaic acid and 1,9-Nonanediol, and 1,7-heptamethylene di-isocyanate (HPMDI) all sourced from vegetable oil feedstock. The thermal, and mechanical properties, and crystal structure of PEUs were investigated using DSC, TGA, DMA, tensile analysis and WAXD. For sufficiently long polyester chain, WAXD data indicated no hydrogen bonds polyethylene (PE)-like crystalline packing and for short polyester chains, small crystal domains with significant H-bonded polyamide (PA)-like packing. Crystallinity decreased with decreasing polyester molecular weights. The polymorphism of PEUs and consequently their melting characteristics were found to be largely controlled by polyester segment length. TGA of the PEUs indicated improved thermal stability with decreasing polyester chain length, suggesting a stabilization effect by urethane groups. Mechanical properties investigated by DMA and tensile analysis were found to scale predictably with the overall crystallinity of PEUs. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Lipid-based poly(ester-urethane); Thermoplastic polyurethanes; Ester to urethane ratio